(untitled) (Malay Literature, 2012)
The paper is an attempt to read two tales about women by a woman narrator with an underlying assumption that only a woman could possibly represent a more authentic female life, and thus her story about women would invariably repudiate other so-called "untrue" formulations about women. With that as a premise, the paper would proceed to unfold the re-imagining or rather the re-visioning of women in the two tales; and this would demand, so to speak, a more unconventional critical method of analysis (benefiting in many ways the feminist strategy of reading) to discover the technique and strategy of repositioning the women characters in the two tales. The paper concludes with two rather uneasy propositions: the texts do give a refreshing presentation of female power in an environment of male hegemony, but the powerful women are not in any way a threat to the patriarchy; as a matter of fact, they help uphold the patriarchal order of things. Keywords: folk tales, re-visioning women character, female power, male hegemony, feminist reading strategy